(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article discusses the impact of globalization on media language. In modern life, globalization is growing very fast because of the internet, television, and social media. People from different countries can easily connect and share information. Because of this, media language is changing and becoming more similar in many parts of the world.